Kemampuan Mengajar Mahasiswa PPL Pendidikan Bahasa Jepang Angkatan 2016 UNNES Ditinjau dari Penilaian Guru Pamong dan Penilaian Diri - Diner, Lispridona; Rohmatulloh, Fajar (Chi'e: Journal of Japanese Learning and Teaching, 2021)
The author conduct this research with the goal to find out the teaching ability of PPL's college students of Japanese language education 2016 UNNES based on self and tutor's assessment. Teaching practice experienced (PPL) is a course with the goal to train college students of educational studies programs to apply they knowledge during lectures in their practice places (school partner) for one and a half months.The approach methode in this research is quantitative descriptive. The sample of this research was 25% of PPL's college students of Japanese language education 2016. The data collection technique used the PPL's assessment scale and questionnaire. The results of data obtained were analyzed used the descriptive percentage techniques.